Maqasid al-shariah comparison to the concept of accounting in the paradigm of religiosity / Syahril ... [et al.] - Syahril, .; Abrori, Faizul; Mohammed, Nor Farizal; Mohamad, Norazida (Universiti Teknologi MARA Selangor, 2024)
The purpose of this study is to describe the comparison of Maqāṣid alSharīʿah with the concept of accounting in the religiosity paradigm. In this study, the authors used a qualitative methodology through a literature survey examining the normative aspects of Maqāṣid alSharīʿah related to accounting. This study analyses experts' minds whose main ideas have been scattered in some literature. Firstly, the concept of accounting is based on Maqāṣid al-Sharīʿah Hifz al-Dīn, where accounting is not only oriented to material elements but also has the responsibility of financial activities to God and religion. Secondly, the accounting concept based on Maqāṣid al-Sharīʿah Hifz al-Nālīs significantly develops offspring into family-oriented balance sheets in the context of the afterlife. Thirdly, the accounting concept based on Maqāṣid al-Sharīʿah Hifz al-Aql makes accounting pious, intellectual, and socially righteous. Fourth, the accounting concept based on Maqāṣid al-Sharīʿah Hifz al-Nafs is the process of elevating the family's status in terms of financial activities. Fifth, it is not only the welfare of certain groups; the accounting concept based on Maqāṣid al-Sharīʿah Hifz al- Māl prioritises social concerns and pays attention to economic development and human interest in creating wealth. Indeed, the Maqāṣid al-Sharīʿah paradigm emphasises social accountability, which prompts more future research in this area.